FRI0142 Patient-Reported Disease Activity and Outcome in Male versus Female Patients of the Groningen Leeuwarden Axial Spondyloarthritis (GLAS) Cohort. (10th June 2014) - Arends, S.; Maas, F.; van der Veer, E.; Bos, R.; Efde, M.; Leijsma, M.K.; Bootsma, H.; Brouwer, E.; Spoorenberg, A.
Abstract : Background: There are differences in clinical presentation of ankylosing spondylitis (AS). Women tend to have milder disease and may therefore be underdiagnosed. Male AS patients are more likely to develop spinal radiographic damage. Objectives: The aim of the present study was to investigate whether there are differences in patient-reported assessments of disease activity, physical function, and quality of life between male and female patients with axial spondyloarthritis (SpA). Methods: All consecutive patients from the Groningen Leeuwarden Axial SpA (GLAS) cohort who visited the outpatient clinic between January 2011 and December 2012 were included in this cross-sectional analysis. All patients fulfilled the modified New York criteria for AS (>90%) or the ASAS criteria for axial SpA. Disease activity was assessed using Bath AS disease activity index (BASDAI), AS disease activity score (ASDAS; calculated from BASDAI questions 2, 3 and 6, patient global assessment of disease activity (GDA), and C-reactive protein (CRP)), swollen joint index (range 0-44), and tender joint index (range 0-46). Physical function was assessed using Bath AS functional index (BASFI) and quality of life using AS quality of life (ASQoL) questionnaire. Results: Of the 469 included patients, mean age was 45 years (SD ±13), mean duration of symptoms was 17 years (range 0-61), 66% were male, and 80% were HLA-B27+. Males were significantly older, had longer disease duration, and were more frequently HLA-B27+ compared to females. Extra-articular manifestations, comorbidity, and current use of NSAID, DMARD, and anti-TNF were comparable between both groups. Patient-reported measures of disease activity (BASDAI, patient GDA, and tender joints) and outcome (BASFI and ASQoL) were significantly higher in female compared to male patients. ASDAS, capturing both subjective and objective aspects of disease activity, was also significantly higher in females. This difference can be explained by patient-reported aspects of the ASDAS, since CRP levels were comparable between male and female patients (Table 1 ). Differences remained statistically significant after correcting for age, disease duration, and HLA-B27 status. Conclusions: This cross-sectional study shows that patient-reported measures of disease activity and outcome as well as ASDAS were significantly worse in female axial SpA patients. We recommend to be aware of these differences when interpreting patient-reported measures in research and clinical practice. Acknowledgements: The GLAS cohort was supported by an unrestricted grant from Pfizer. Pfizer had no role in the design, conduct, interpretation, or publication of this study. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4330